Journalistic Texts in Training Russian as Foreign Language: Genre-Orientation Approach; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Vorobyova L. V. Lyudmila Vladimirovna (2015, 2015)
Title screen